Three-dimensional illumination analysis in pipe-like complexities by ray-tracing modeling - Cui, Zhihua; Tan, Feng; Taiwo, Olusoji Lawrence (Frontiers in Earth Science, 2025)
Pipe-like formations are vertical, complex and shape-diverse subsurface structures. The accurate seismic interpretation is essential for understanding their fluid dynamics and environmental impacts. However, conventional seismic exploration techniques struggle to accurately resolve their critical areas due to a general decline in imaging quality. This challenge is significant due to their three-dimensional nature, as some exaggerated forms impact seismic imaging, despite appearing similar in 2D slices. This limited perspective is commonly used in the oil and gas industry. This study uses a forward solution based on ray-tracing modeling specifically designed for illumination studies to help understand the impact of boundary on illumination variation, complemented by robust geometric models and elastic information derived from reasonable interpretations. We explore the impact of boundary edge curvature on illumination. The findings indicate that low curvature edges allow more rays to penetrate deeper into the boundary areas, potentially achieving higher illumination. The potential distribution of low-illumination or shadow zones are then proposed on the horizontal attribute at the top of the root area, which may explain why internal structures are often poorly imaged. This suggests the possibility of internal ray preclusion, leading to local multiples that cannot be effectively received. This research supports and enhances the understanding of why conventional seismic methods have difficulty in fully addressing imaging quality for such complex structures. It provides a thoughtful basis for further geological interpretation of this and similar vertical structures under the constraints of seismic imaging technology.